EFFECTS OF PHYSICAL ACTIVITY PROGRAM BY APPLYING SOCIAL AND EMOTIONAL LEARNING TO PROMOTE MENTAL HEALTH AND SOCIAL WELL - BEING OF LOWER SECONDARY SCHOOL STUDENTS - Teerawattanaprasit, Nisarat; Sarayuthpitak, Jintana; Yasiersat, Chakree; Phroedphring, Chatchana (Academic Journal of Thailand National Sports University, 2022)
The purpose of this research was to study the effects of physical activity program by applying social and emotional learning for promoting mental health and social well - being of lower secondary school students. The subjects consisted of 60 lower secondary school students, divided into 2 groups, 30 students in the experimental group, and 30 students in the control group. The research instruments were the physical activity program by applying social and emotional learning consisting of eight activities with IOC 0.98, the mental assessment form with IOC 0.96, reliabilities 0.95, and the social well - beings assessment form with IOC 0.81, reliabilities 0.96 the research period was 8 weeks, 3 days per week, 1 hour per day. The data were analyzed using mean, standard deviation and t - test. The research findings were as follows: the mean scores of mental and social well-beings of the experimental group students after the experiment were statistically significant higher than before at the .05 level, and the mean scores of mental and social well - being of the experimental group students after the experiment were statistically significant higher than the control group at the .05 level. This showed that the physical activity program by applying social and emotional learning had an effect on the mental health and social well - beings of lower secondary school students.